Replication of the Association of BDNF and MC4R Variants With Dietary Intake in the Diabetes Prevention Program. Issue 2 (February 2017) - McCaffery, Jeanne M.; Jablonski, Kathleen A.; Franks, Paul W.; Delahanty, Linda M.; Aroda, Vanita; Marrero, David; Hamman, Richard F.; Horton, Edward S.; Dagogo-Jack, Samuel; Wylie-Rosett, Judith; Barrett-Connor, Elizabeth; Kitabchi, Abbas; et al.
ABSTRACT: Objective: Genomewide association studies (GWAS) have identified consistent associations with obesity, with a number of studies implicating eating behavior as a primary mechanism. Few studies have replicated genetic associations with dietary intake. This study evaluates the association between obesity susceptibility loci and dietary intake. Methods: Data were obtained as part of the Diabetes Prevention Program (DPP), a clinical trial of diabetes prevention in persons at high risk of diabetes. The association of 31 genomewide association studies identified obesity risk alleles with dietary intake, measured through a food frequency questionnaire, was investigated in 3, 180 participants from DPP at baseline. Results: The minor allele at BDNF, identified as protective against obesity, was associated with lower total caloric intake (β = −106.06, SE = 33.13; p = .0014) at experimentwide statistical significance ( p = .0016), whereas association of MC4R rs571312 with higher caloric intake reached nominal significance (β = 61.32, SE = 26.24; p = .0194). Among non-Hispanic white participants, the association of BDNF rs2030323 with total caloric intake was stronger (β = −151.99, SE = 30.09; p < .0001), and association of FTO rs1421085 with higher caloric intake (β = 56.72, SE = 20.69; p = .0061) and percentage fat intake (β = 0.37, SE = 0.08; p = .0418) was also observed. Conclusions: These results demonstrate with the strength of independent replication that BDNF rs2030323 is associated with 100 to 150 greater total caloric intake per allele, with additional contributions of MC4R and, in non-Hispanic white individuals, FTO . As it has been argued that an additional 100 kcal/d could account for the trends in weight gain, prevention focusing on genetic profiles with high dietary intake may help to quell adverse obesity trends. Clinical Trial Registration: Clinicaltrials.gov, NCT00004992 . Abstract : Supplemental digital content is available in the text.